Dental microwear and Pliocene paleocommunity ecology of bovids, primates, rodents, and suids at Kanapoi. Issue 140 (March 2020) - Ungar, Peter S.; Abella, Elicia F.; Burgman, Jenny H.E.; Lazagabaster, Ignacio A.; Scott, Jessica R.; Delezene, Lucas K.; Manthi, Fredrick K.; Plavcan, J. Michael; Ward, Carol V.
Abstract: Reconstructions of habitat at sites like Kanapoi are key to understanding the environmental circumstances in which hominins evolved during the early Pliocene. While Australopithecus anamensis shows evidence of terrestrial bipedality traditionally associated with a more open setting, its enamel has low δ 13 C values consistent with consumption of C3 foods, which predominate in wooded areas of tropical Africa. Habitat proxies, ranging from paleosols and their carbonates to associated herbivore fauna and their carbon isotope ratios, suggest a heterogeneous setting with both grass and woody plant components, though the proportions of each have been difficult to pin down. Here we bring dental microwear texture analysis of herbivorous fauna to bear on the issue. We present texture data for fossil bovids, primates, rodents, and suids ( n = 107 individuals in total) from the hominin bearing deposits at Kanapoi, and interpret these in the light of closely related extant mammals with known differences in diet. The Kanapoi bovid results, for example, are similar to those for extant variable grazers or graze-browse intermediate taxa. The Kanapoi suid data vary by taxon, with one similar to the pattern of extant grazers and the other more closely resembling mixed feeders. The Kanapoi primates and rodents are more difficult to associate with a specific environment, though it seems that grass was likely a component in the diets of both. All taxa evince microwear texture patterns consistent with a mosaic of discrete microhabitats or a heterogeneous setting including both tree and grass components.